Iš baltų etimologijos - Mažiulis, Vytautas (Baltistica, 2007)
FROM BALTIC ETYMOLOGY (1. “SIEVE” AND “PLEIADES”; 2. LITH. Medvė́galis; 3. LITH. ŽEM. Tvẽrai) 1. The form pr. E (346) baytan “sieve” should be corrected to Pr. (E) *saytan “id.” = Pr. *saitan “id.”, while this is derived from balt. *seitan “id.” (neutr.), which was not only “sieve”, but also “Pleiades” (an astronomical term). Later on the following formed: a) For Eastern Balts next to the form *seitan (neutr.) “sieve; Pleiades” its suffix derivative *Seitīna- “Pleiades” (seems to be neutr.) and b) for Western Balts next to the form *seitan “sieve; Pleiades” suffix derivative *Seitāran “Pleiades” (neutr.); the last being shown by its form (E 6) *Paytoran „id.“, should be corrected to *Saytoran = pr. *Paitāran „id.“ (neutr.), which probably derives from Western Balt. *Seitāran „id.“ (neutr.). The word is Baltic, i.e. Balt.-Sl. *seitan “sieve” – the derivative of the suffix *-ta- is from the presentic stem from the old Balt.–Sl. verb *sē-ti “to sift, sieve”. 2. The name Medvėgalis (the ía- stem), which is the name of a large hilly area with small rivers fed by underground well, is a composition with a second component of -galīs from galas, meaning “corner, place”. The component Medvē-, which should not be linked with Žem. mẽdė “forest”, the little river’s name supposed by Cur. *Med(u)vē, flowing through a Curonian sacrificial place (a holy site). The gender of *Med(u)vē (up.) from the older Cur., *Med(u)vā is the suffix’s *-(u)vā- derivative from subst. Curonian (Balt.) *medu “honey” (neutr.). Such an etymology of the river’s name is supported by the river’s holyness (because of the sacrificial place) and especially the fact, that its water was clean because of the currents (where it flowed along the banks) and was clear like fresh linden honey (it seems that for the Balts, honey was holy). 3. The name of the old Samogitian settlement called Tvẽrai, mentioned numerous times in the writings of the Teutonic Order dating from the 13th-14th century, first of all arose in the form Rus. (1251) Твиреметь (Твиременть), the origin of which is unclear. Now it has become clear, that this Russian form reflects the Lith. (Žem.) composition *Tveramedīs “Forest of Tverai” (ía-kamienį), which is: *Tvera- (= sing. *tveras “enclosure”) + *-medīs (< Žem. mẽdė “forest”). Next to the form Lith. (Žem.) *tveras “enclosure” would have been from Lith. (Žem.) *tverta- “id.”. Both synonyms are from Lith. (Žem.) *tvaras “id.” resp. *tvarta- “id.” – a suffixed derivative from the verb Cur. (Balt.) *tvar- “to enclose”.